Ab initio study of the nature and stability of the defects and multi-vacancies in TaN. Comparison with TiN. (30th December 2016) - Boulat, Laetitia; Fréty, Nicole; Sans, Pierre; Viennois, Romain
Abstract: First principles calculations have been carried out to study the native single-defects and multi-vacancies in TaN and TiN with a cubic rocksalt structure mainly used as diffusion barriers. Our results indicate that vacancies are the most stable single-defects in both compounds and that nitrogen interstitial defects in tetrahedral interstitial site are significantly more stable in TaN than in TiN. The interactions between vacancies are attractive in TaN in contrast to the case of TiN. The vacancies show a much larger tendency to cluster and to form bi- and tri- vacancies in TaN than in TiN. We suggest that the number of d electrons might explain this difference in the defect stability. These results will have impact on the use of these materials as diffusion barrier.